(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Among countries with comparable levels of income, Indiahas one of the more progressive disability policy frameworks. However, peoplewith disabilities in India are subject to multiple disadvantages. This paperfocuses on state-level variations in outcomes for people with disabilities toprovide an explanation for the stark contrast between the liberal laws on paperand the challenges faced by people with disabilities in practice. Using averagemonthly per capita expenditure as an indicator of economic well-being,instrumental variables Wald estimator with state fixed-effects results indicatethat households with members with disabilities have expenditures that are 14percent lower as compared to households with able members. This effect is mostpronounced among families with male adults and children with disabilities, andin states that are relatively poor, relatively more urban, those thatexperience extremes in annual rainfall and temperature, and those that have lowto medium levels of inequality.